P3DM: Mapping for sustainable agriculture in Sasatgre, India - Chakraborty, Sanat K. (Technical Centre for Agricultural and Rural Cooperation, 2005)
Sanat K. Chakraborty explains how participatory 3D modelling has helped an isolated hill community to optimize the use of their land.